2009
DOI: 10.1021/ol9013377
|View full text |Cite
|
Sign up to set email alerts
|

Competing Domino Processes: Path-Discriminating Ability of Epoxide Stereochemistry at the Angular Position

Abstract: Structurally different products can be reached selectively from unsaturated vicinal bicyclic diols, which differ only by the epoxide configuration at the angular position. It is possible to modify the regiochemical outcome of the domino process in such a way as to create a different pathway, [4 + 2] versus [4 + 3 + 2], and control product distribution by using the configuration bias. No previous example of a domino variant of the [4 + 3 + 2] process appears to have been documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One C-C bond brakes, an oxirane ring opens and three new C-O bonds are formed in a single synthetic operation at rt (Scheme 53). 97 Unlike the corresponding (11R ⁄ )-epimer, the (11S ⁄ )-epimer cannot evolve through the hetero[4+3+2] pathway via iii for obvious sterochemical reasons, and follows the [4+2] cycloaddition via ii and a subsequent epoxonium induced deplumbation on iv. The vital requirement of this hetero[4+2] cycloaddition/oxyplumbation/deplumbation sequence is that an epoxide is amply nucleophilic to displace the Pb(OAc) 3 via a transient epoxonium formation (iv to 19bg).…”
Section: Domino Probes Tethered To An Epoxide Ringmentioning
confidence: 99%
“…One C-C bond brakes, an oxirane ring opens and three new C-O bonds are formed in a single synthetic operation at rt (Scheme 53). 97 Unlike the corresponding (11R ⁄ )-epimer, the (11S ⁄ )-epimer cannot evolve through the hetero[4+3+2] pathway via iii for obvious sterochemical reasons, and follows the [4+2] cycloaddition via ii and a subsequent epoxonium induced deplumbation on iv. The vital requirement of this hetero[4+2] cycloaddition/oxyplumbation/deplumbation sequence is that an epoxide is amply nucleophilic to displace the Pb(OAc) 3 via a transient epoxonium formation (iv to 19bg).…”
Section: Domino Probes Tethered To An Epoxide Ringmentioning
confidence: 99%
“…The precise mechanistic rationale underpinning these contrasting pericyclic pathways is still under investigation. 23 In a rare example of the use of an electrocyclization for the formation of a medium ring, Suzuki and co-workers reported an electrocyclic ring-opening/ring-closing cascade for the generation of 2-benzoxocin derivatives (Scheme 11). 24 The group reported that heating a toluene solution of 1-acyloxybenzocyclobutene 63 resulted in a mixture of 2-benzoxocin 64 and naphthalene 65, with 64 being the major product observed.…”
Section: Pericyclic Cyclizations and Cycloaddition Reactionsmentioning
confidence: 99%
“…Our investigations resulted in efficient ways to construct complex molecular frameworks in one pot by planned combination of reactive groups placed at the angular position. Thus, it is possible to select a ring‐expanding path,2 a hetero[4π+2π+2π]cycloaddition,3 a ring‐retentive oxonium path,4 or a hetero[4+3+2]cycloaddition5 by varying the functional group at the angular position or simply to interrupt the process at the [4π+2π] stage 6. Establishing a fundamental mechanistic understanding in these domino reactions,7 discovered by serendipity, led to the development of new variations and improved our capacity to predict reactivity.…”
Section: Introductionmentioning
confidence: 99%